(untitled) - Downer, Lesley (New York, 1994)
The epic, untold story of the men behind Japan's greatest business dynasty, and their rise from obscurity to extreme wealth and power, The Brothers recounts the public and private lives of the Tsutsumi family, who are to Japan what the Rockefellers or the Gettys are to the West.
Keywords: Businessmen,Executives; Biography,Biography; Japan,Japan